Sistem Informasi Pemilihan PTN Pada Sekolah Menengah Tingkat Atas Negeri 4 Bogor - Nining Suryani; Maulana Rizki; Evy Priyanti (IMTechno: Journal of Industrial Management and Technology, 2022)
The growth of several universities in Indonesia indicates that the knowledge gained is important for life or for finding work. The process of selecting universities, especially public universities for students is a complicated process and they may make a mistake in choosing a public university which in the end makes them feel they have wasted a lot of time. Therefore, the need for a computer-based system is deemed necessary to meet the information needs. This study uses the SDLC and waterfalls methods while the data collection is done by using the methods of observation, interviews, and literature study. The determination of the selection of this university will use the Analytical Hierarchy Process (AHP) method as a determinant of the weight of each criterion to determine the priority of each university. For the manufacture of this system used the Unified Modeling Language (UML) design model. This study aims to produce a system design that can be used for the selection of state universities and can assist in providing evaluations based on student and student criteria, including location, accreditation, scholarships, facilities and SMEs.